A Priority Crime that is not a Priority? The Illegal Cigarette Trade: A Case Study of Mowbray - McLaggan, Michael Taylor (Department of Public Law, 2020)
Objective: To determine how prevalent the illegal trade in cigarettes is in Mowbray, whether buyers thereof are aware of the illegal nature of their purchases, and whether they would transition to buying legal products if they became aware of the illegal nature of their purchases. Methods: Observations of stores throughout Mowbray were used to determine which stores sold illegal cigarettes, using price of packs of cigarettes as a determinant for illegality. Surveys were conducted using smokers in Mowbray as subjects in order to understand preferences of these subjects in terms of which products they bought and at which type of store they bought from. An interview was conducted with a Brigadier of the Directorate for Priority Crimes in order to understand how illegal cigarettes are policed in the country. Results: The research shows that cigarettes in Mowbray are very accessible and popular amongst consumers. It further demonstrates that most consumers of illegal products are aware of the illegal nature of their purchases and would not transition to legal products if it meant paying higher prices. Conclusions: The prevalence of illegal cigarettes is a result of the failure of state institutions to adequately address the issue. The popularity amongst consumers stems from the high availability of illegal cigarettes and the low prices thereof. Responses of state institutions tasked with addressing the illegal trade are essential in order to combat the trade.